Performance of Companies after Business Rescue In South Africa - Wu, Biyu (University of the Witwatersrand, Johannesburg, 2023)
This study investigated the performance of the companies that went through business rescue in South Africa, and the impact of such program on the viability of firms. The purpose of a business rescue program is to rehabilitate struggling businesses. The business rescue program provides a number of initiatives, namely a temporary supervision of the business and its affairs, business and property; a temporary moratorium on the rights of claimants against the business or in respect of property in its possession; and the development and implementation of the business rescue program. The business rescue program has three major processes. Firstly, a business rescue practitioner will be appointed and he will oversee the business, its property and the management of the business affairs. Secondly, the business will be shielded from all creditors’ claims. The purpose of the second step is for the rescue practitioner to carry out the third process, where he will restructure the business, property, debt, affairs, liabilities, and equity, among other things. This study evaluated the impact of the above process through analysing the performance of the rescued companies in South Africa. By using a treatment effect methodology and a dataset for firms in the media and real estate industries for the period 2011 to 2019, the study found a positive and strong impact of the business rescue program on struggling firms. Firms that went through the business rescue programs have been observed to be more profitable, better able to accumulate assets, better able to manage cash flows and creditors and they were also able to attract investors. However the impact of the business rescue program has been observed to be disproportionately different across industries. Thus, policy makers have been recommended to expand on the program, to create industry specific business rescue programs, and to enhance the business environment for the companies at their post rescue period, including introducing policies to incentivize the investors and to offer tax rebates to the rescued businesses
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Business rescue; Firms; Treatment effect; Viable; Profitable; UCTD; SDG-8: Decent work and economic growth